2013
DOI: 10.1590/s0044-59672013000200011
|View full text |Cite
|
Sign up to set email alerts
|

Capacidade da Lemna aequinoctialis para acumular metais pesados de água contaminada

Abstract: A capacidade das plantas em tolerar e absorver quantidades elevadas de metais pesados é usada como uma tecnologia promissora para limpeza de resíduos perigosos em ambientes altamente contaminados. O desempenho da macrófita L. aequinoctialis em absorver metais pesados foi estudado durante sua floração em dois períodos de amostragem diferentes. Ability of Lemna aequinoctialis for removing heavy metals from wastewater ABSTRACTPlant ability for tolerating and accumulating high amount of heavy metal is used as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
0
12
0
9
Order By: Relevance
“…No Cr(VI) contamination was observed in IgQ waters when collecting the biological samples, but historical monitoring records of that bayou waters presented high levels of total chromium (between 158.4 ± 164.6 mg/L), according to Pio et al (2013). The National Environmental Council legislation in force in Brazil (CONAMA 2011), for effluent releases, establishes that the maximum level of Cr(VI) permitted is 0.1 mg/L.…”
Section: Resultsmentioning
confidence: 92%
“…No Cr(VI) contamination was observed in IgQ waters when collecting the biological samples, but historical monitoring records of that bayou waters presented high levels of total chromium (between 158.4 ± 164.6 mg/L), according to Pio et al (2013). The National Environmental Council legislation in force in Brazil (CONAMA 2011), for effluent releases, establishes that the maximum level of Cr(VI) permitted is 0.1 mg/L.…”
Section: Resultsmentioning
confidence: 92%
“…The composition of Rex3 in tamoatás from the Quarenta stream, which has industrial waste and domestic sewage in its waters, 18,73 showed stronger signals than that in tamoatás from the Mindu stream, which has contaminants from domestic sewage and organic residues. Furthermore, detected variations in the increase in pH, high conductivity values, low dissolved oxygen levels, and high concentrations of cations and anions in the waters of these streams, with higher values in the Quarenta stream, suggest that changes in these ecosystems are related to the origins of pollution sources.…”
Section: Discussionmentioning
confidence: 90%
“…The use of plants and microorganisms is an important tool in the removal processes of different classes of pollutants in aquatic and terrestrial ecosystems (Farnese et al, 2014;Pio et al, 2013). Traditional methods of removing heavy metals from effluent, when at low concentrations, may be expensive and present very little selectivity and yield (Silva et al, 2014).…”
Section: Introductionmentioning
confidence: 99%